Kreativitas, Inovasi, dan Keberhasilan usaha: Studi kasus pada Usaha Kuliner Tradisional Jepa di Masa Pandemi Covid 19 - Siti Maryam; Agus Syam; Muhammad Hasan; Muhammad Dinar (INSIGHT: Indonesian Journal Social Studies and Humanities, 2022)
Abstract. This study aims to determine creativity, innovation, and business success: a case study on a traditional Japanese culinary business during the covid 19 pandemic. This study uses a descriptive qualitative method. Data collection techniques through observation, interviews, and documentation. The informants were determined based on the criteria determined by the researcher, namely the Japanese seller in Pamboang, Majene. The results of this study indicate that the creativity and innovation of Japanese sellers are very helpful in achieving business success during the covid 19 pandemic. The potential of traditional Japanese culinary sellers in Paboang District, Majene in increasing business success is very demanding in creating creativity and innovation. This gives the ability of traditional Japanese culinary sellers in Paboang District, Majene to compete during the covid 19 pandemic. Creativity and innovation that is currently owned can continue to be developed so that business success continues to increase.Keywords:Creativity, Innovation, Business Success